# Chemistry

posted by .

.50 - x / x = 3.20e-1

I need to solve for x. I was going to do .50 X 3.20e-1 and then take the square root but this is not correct. I am not sure what to do. Thank you for your help.

You probably meant

(.50 - x)/x = 3.2 e^-1= 3.2/e
crossmultiply ...
.50 - x = (3.2/e)x
(3.2/e)x + x = .5
x(3.2/e + 1)
x = .5/(3.2/e + 1)
multiply by e/e
= .5e/(3.2 + e)
multiply by 10/10
= 5e/(32 + 10e)

So I have to multiply 5e by 10 which would be 50e and then multiply (32+10e) by 10?

Math(Please respond) - bobpursley, Wednesday, April 18, 2012 at 7:17pm
Hannah: Professor Reiny solved it for you.

x= 10e/(32+10e)

calculate that. Or if you cant, put this in your google search window

10*e/(32+10*e) =

I understand. If the number was 2.49e-1 I would do the same thing, so it would be 10*e / (249 + 10*e) = ?. Is this correct?

• Chemistry -

I started to write this a couple of days ago when I saw this post but didn't. Frankly, I thought both professor Reiny and professor Pursley misinterpreted the question. I still think so. I don't think it has anything to do with e. I believe you meant
[(0.50-x)/x] = 3.20E-1 which I would rewrite as
0.320 = (0.50-x)/x, then
0.320x = 0.50-x
1.320x = 0.50 and
x = 0.50/1.320
x = ?

• Chemistry -

Ok thank you the way you have it is exactly the way that it was stated on my homework. The only problem is that I realized that I had the typed the wrong number. It was suppose to be the same equation but with 2.49e-1 instead 3.20e-1. I understand everything except how did you get 1.320?

• Chemistry -

0.320 = (0.50-x)/x, then
0.320x = 0.50-x
0.320x = 0.50 -x
0.320x + x = 0.50 -x +x
0.320x + 1x = 0.50
1.320x = 0.50 and
x = 0.50/1.320.

1.320x = 0.50 and
x = 0.50/1.320

• Chemistry -

Thank you.

## Similar Questions

1. ### Math

What are the solution sets of the following 3 problems,the square root of x squared + 3x = x-3, the square root of 3x + 10 = x + 4 and finally the square root of 8x - 2 = the square root of 2x?
2. ### Math

Precalc stuff.. square root of z-1= square root of z +6 are you solving for z?
3. ### algebra

1.)correct 2.)wrong---> the first term is wrong 4(3a^2)^2 = 36a^4 3.) not sure on this one 4.) wrong---> - square root of six is not a solution Hope this Helps! 1)find p(-3)if p(x)=4x^3-5x^2+7x-10 =-184 2)If r(x)=4x^2-3x+7,find …
4. ### algebra

1)Write the expression 9n^6+7n^3-6 in quadratic form,if possible A.9(n^3)^3+7n^3-6 B.9(n^2)^3+7(n^2)-6 C.9(n^3)^2+7(n^3)-6 D.not possible I'm thinking C on this one but im not sure 2)solve b^4+2b^2-24=0 A.-2,-square root of 6,square …
5. ### Algebra

Use the quadratic formula to solve the equation. Give exact answers: 2x^2 -1 = 6x. The choices are: a) -3 + square root(7)/2, -3 - square root(7)/2 b) 3 + square root(11)/2, 3 - square root(11)/2 c) 3 + square root(7)/2, 3 - square …
6. ### algebra 2

Not sure if either one of these answer are correct to simplify the sqrt for 24 1) 24 = 6 x 4 square root of 24 = square root of 6 x 4 2 root 6 2) sq root 24 = sq root (4x6)= sqrt 4 x sqrt 6= 2sq root 6=4.89898 3) Square root of 24 …